Impact of tapping and soil water status on fine root dynamics in a rubber tree plantation in Thailand - Chairungsee, Naruenat; Gay, Frédéric; Thaler, Philippe; Kasemsap, Poonpipope; Thanisawanyangura, Sornprach; Chantuma, Arak; Jourdan, Christophe (Frontiers in Plant Science, 2013)
Fine roots (FR) play a major role in the water and nutrient uptake of plants and contribute significantly to the carbon and nutrient cycles of ecosystems through their annual production and turnover. FR growth dynamics were studied to understand the endogenous and exogenous factors driving these processes in a 14 year-old plantation of rubber trees located in eastern Thailand. FR dynamics were observed using field rhizotrons from Oct. 2007 to Oct. 2009. This period covered two complete dry seasons (Nov.-Mar.) and two complete rainy seasons (Apr.-Oct.), allowing us to study the effect of rainfall seasonality on FR dynamics. Rainfall and its distribution during the two successive years showed strong differences with 1500 mm and 950 mm in 2008 and 2009, respectively. Fine root production (FRP) completely stopped during the dry seasons and resumed quickly after the first rains. During the rainy seasons, FRP and the daily root elongation rate (RER) were highly variable and exhibited strong annual variations with a total FRP of 139.8 and 40.4 m m-² and an average RER of 0.16 and 0.12 cm d-1 in 2008 and 2009, respectively. The significant positive correlations found between FRP, RER, the appearance of new roots and rainfall at monthly intervals revealed the impact of rainfall seasonality on FR dynamics. However, the rainfall patterns failed to explain the weekly variations of FR dynamics observed particularly during the rainy seasons. At this time step, FRP, RER and the appearance of new FR were negatively correlated to the average soil matric potential measured at a depth of between 30 and 60 cm. In addition, our study revealed a significant negative correlation between FR dynamics and the monthly production of dry rubber. Consequently, latex harvesting might disturb carbon dynamics in the whole tree, far beyond the trunk where the tapping was performed. These results exhibit the impact of climatic conditions and tapping system in the carbon budget of rubber plantations.